Peningkatan Keterampilan Komunikasi Efektif Petugas Kader Posyandu Dalam Memberikan Pelayanan di Rw 01 Pademangan Timur Jakarta - Ria Efkelin; Sarah Geltri Harahap; Martini Martini; Ary Rahmaningsih; Imelda Imelda (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Posyandu plays a crucial role in improving community welfare in various regions, and the presence of health cadres as the spearhead of Posyandu implementation. The purpose of this activity is to enhance the ability of Posyandu cadres in providing services through effective communication skills improvement. The methods used in this activity include lectures, discussions, question-and-answer sessions, as well as pre-tests and post-tests. The results of this activity show a significant increase in the effective communication skills of Posyandu cadres. This increase can be seen from the gain score values that improve the effective communication skills of Posyandu cadres. Participant S achieved the highest gain score value of 0.9 and a percentage increase of 90.0%.